Increase in passive muscle tension of the quadriceps muscle heads in jumping athletes with patellar tendinopathy - Zhang, Z. J.; Ng, G. Y. F.; Lee, W. C.; Fu, S. N. (Scandinavian Journal of Medicine & Science in Sports, 2017)
To investigate the passive muscle tension of the quadriceps muscle heads in male athletes clinically diagnosed with patellar tendinopathy (PT) with those of healthy controls and explore the interplay between passive muscle tension and patellar tendon stiffness. Between November 2012 and December 2013, 66 male athletes (mean age of 21.1 ± 4.4 years) were examined using supersonic shear wave imaging technology. The passive tension of the vastus lateralis (VL) and rectus femoris (RF) muscles and patellar tendon stiffness were assessed. The shear elastic modulus of the VL muscle was increased by 26.5% (P < 0.001) in the subjects with PT when compared with the controls. Greater passive tension in the VL was associated with higher patellar tendon stiffness (r = 0.38; P = 0.001). The vastus lateralis muscle of the quadriceps shows increase in passive muscle tension in jumping athletes with patellar tendinopathy. These findings suggest that increase in muscle tension is not similar in the individual muscles of the quadriceps muscle. Traditional stretching of the whole quadriceps muscle might not be targeted to the tight muscle heads.